2013
DOI: 10.1007/s11104-012-1580-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of aluminium and drought stress on root growth and crop yield on acid soils

Abstract: Background Aluminium (Al) toxicity and drought stress are two major constraints for crop production in the world, particularly in the tropics. The variation in rainfall distribution and longer dry spells in much of the tropics during the main growing period of crops are becoming increasingly important yield-limiting factors with the global climate change. As a result, crop genotypes that are tolerant of both drought and Al toxicity need to be developed. Scope The present review mainly focuses on the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 210 publications
1
80
0
6
Order By: Relevance
“…The correlation between the RNAseq and qRT-PCR data was highly significant (r 2 = 0.85, P < 0.001) (Supplemental Figure 11D). The rapid binding of Al to the cell wall matrix is expected to alter the properties of the cell wall and thereby affect root growth (Tabuchi and Matsumoto, 2001;Ma et al, 2004;Horst et al, 2010;Yang et al, 2013). Several genes related to cell wall structure and composition, including those encoding xyloglucanases, endotransglycosylases, polygalacturonases, and glycosyl transferases, have been identified as being involved in the regulation of Al tolerance or the Alinduced inhibition of root growth (Kumari et al, 2008;Maron et al, 2008;Tsutsui et al, 2012;Zhu et al, 2012).…”
Section: The Arf10/16 Double Mutant Has a Differential Transcriptionamentioning
confidence: 99%
“…The correlation between the RNAseq and qRT-PCR data was highly significant (r 2 = 0.85, P < 0.001) (Supplemental Figure 11D). The rapid binding of Al to the cell wall matrix is expected to alter the properties of the cell wall and thereby affect root growth (Tabuchi and Matsumoto, 2001;Ma et al, 2004;Horst et al, 2010;Yang et al, 2013). Several genes related to cell wall structure and composition, including those encoding xyloglucanases, endotransglycosylases, polygalacturonases, and glycosyl transferases, have been identified as being involved in the regulation of Al tolerance or the Alinduced inhibition of root growth (Kumari et al, 2008;Maron et al, 2008;Tsutsui et al, 2012;Zhu et al, 2012).…”
Section: The Arf10/16 Double Mutant Has a Differential Transcriptionamentioning
confidence: 99%
“…High aluminum concentrations may have exacerbated the effect of climatic variability by causing greater soil moisture deficits on the acidic plots; aluminum toxicity is known to inhibit root growth (Kochian, 1995;Horst et al, 2010), leading to reduced root length density and shallower rooting depth (Jentschke et al, 2001;Tang et al, 2001) in a variety of species. Physiological relationships between aluminum toxicity, impeded root growth, and drought sensitivity of plants are well established (Yang et al, 2013). Also, Dodd et al (1994b) suggested that the large yield variability of the species-poor, acidic plots on the PGE were related (at least in part) to soil moisture deficits.…”
mentioning
confidence: 98%
“…Phenotypic evaluations of root traits in common bean under drought stress have shown the importance of different rooting patterns, including deep rooting which allows access to water from deeper soil layers (Sponchiado et al 1989;White and Castillo 1992;Lynch and Ho 2005;Polania et al 2009Polania et al , 2012Beebe et al 2013Beebe et al , 2014Rao 2014;Burridge et al 2016). Different ideotypes of root system have been proposed for better crop adaptation to individual and combined abiotic stress conditions (Yang et al 2013;Rao et al 2016). One of the root ideotypes proposed to optimize water and N acquisition is the ''steep, cheap and deep -SCD'' (Lynch 2013).…”
mentioning
confidence: 99%